Analisis Fenomena Pencarian Jodoh Melalui Aplikasi Kencan Tinder Dalam Keterbukaan Diri Pengguna di Kota Samarinda - Hirpa Aulia; Jaka Farih Agustian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
The emergence of the Tinder dating application as a form of technological progress is utilized by many people to meet the needs of human life in finding a life partner. Tinder appears to make it easier for individuals to get acquainted with new people they meet on the internet. The process of communication and interaction changes. In starting a relationship, self-disclosure is the first step in achieving a deep relationship. In this case, the process of self-disclosure is a process of disclosing personal information. Personality disclosure affects the intimacy of a relationship. The purpose of this research is to find out the phenomenon of finding a mate through the Tinder application in the self-disclosure of users in Samarinda city. This research uses a qualitative method with a phenomenological approach and uses Social Penetration theory. The techniques used in collecting data are observation, interviews and documentation of 5 Tinder application users in Samarinda City. Informant collection using purposive sampling technique. Based on the results of the study, the stages of informant self-disclosure in finding a mate through the application are at different stages. Not all informants are at the effective stage, where informants avoid conflict rather than resolve conflicts that occur so that the relationship runs aground before commitment. In the orientation process, selection is made through the user profile in the application, then the process of self-disclosure is carried out outside the application